Gesture deficits and apraxia in schizophrenia. (December 2020) - Walther, Sebastian; Mittal, Vijay A.; Stegmayer, Katharina; Bohlhalter, Stephan
Abstract: Aberrant performance of skilled action has long been noted in schizophrenia and relatedly, recent reports have demonstrated impaired use, performance, and perception of hand gestures in this group. Still, this deficit is not acknowledged as apraxia, which to the broader medical field, characterizes impairments in skilled actions. Understanding the relationship between apraxia and schizophrenia may shed an invaluable new perspective on disease mechanism, and highlight novel treatment opportunities as well. To examine this potential link, we reviewed the evidence for the types of praxis errors, associated psychopathology, and cerebral correlates of the praxis deficit in schizophrenia. Notably, the review indicated that gesture deficits are severe enough to be considered genuine apraxia in a substantial proportion of patients (about 25%). Further, other potential contributors (e.g., hypokinetic motor abnormalities, cognitive impairment) are indeed associated with gesture deficits in schizophrenia, but do not sufficiently explain the abnormality. Finally, patients with praxis deficits have altered brain structure and function including the left parieto-premotor praxis network and these neural correlates are specific to the praxis deficit. Therefore, we argue that the gestural disorder frequently observed in schizophrenia shares both the clinical and neurophysiological features of true apraxia, as in other neuropsychiatric disorders with impaired higher order motor control, such as Parkinson's disease.